Circular RNA 0006349 Augments Glycolysis and Malignance of Non-small Cell Lung Cancer Cells Through the microRNA-98/MKP1 Axis - Qin, Chu; Lu, Rongguo; Yuan, Minyu; Zhao, Rui; Zhou, Huiya; Fan, Xiaodong; Yin, Bo; Yu, Haoda; Bian, Tao (Frontiers in Cell and Developmental Biology, 2021)
Background: The involvement of dysregulated circular RNAs (circRNAs) in human diseases has been increasingly recognized. In this study, we focused on the function of a newly screened circRNA, circ_0006349, in the progression of non-small-cell lung cancer (NSCLC) and the molecules of action. Methods: The NSCLC circRNA dataset GSE101684, microRNA (miRNA) dataset GSE29250, and mRNA dataset GSE51852 obtained from the GEO database were used to identify the differentially expressed genes in NSCLC samples. Tumour and normal tissues were collected from 59 patients with NSCLC. The expression of circ_0006349, miR-98, and MAP kinase phosphatase 1 (MKP1) in collected tissue samples and in acquired cells was determined. The binding relationships between miR-98 and circ_0006349/MKP1 were predicted and validated. Altered expression of circ_0006349, miR-98, and MKP1 was introduced in NSCLC cells to examine their roles in cell growth, apoptosis, and glycolysis. Results: Circ_0006349 and MKP1 were upregulated, and miR-98 was poorly expressed in the collected tumour tissues and the acquired NSCLC cell lines. Circ_0006349 was identified as a sponge for miR-98 to elevate MKP1 expression. Silencing of circ_0006349 suppressed proliferation and increased apoptosis of Calu-3 and H1299 cells, and it reduced glycolysis, glucose uptake, and the production of lactate in cells. Upon circ_0006349 knockdown, further downregulation of miR-98 or upregulation of MKP1 restored the malignant behaviours of cells. Conclusion: This research demonstrated that circ_0006349 derepressed MKP1 expression by absorbing miR-98, which augmented the proliferation and glycolysis of NSCLC cells and promoted cancer development.